Time-Domain Simulation of Semiconductor Laser in Fiber-optic Communication Systems - Zhu, Jiang (My University, 2003)
As the light source, semiconductor laser diodes play an important role in the fiber-optic communication systems. The main function of a laser diode is to convert signals from the electrical domain to the optical carriers so that they can be transmitted through an optical fiber. Modeling and simulation of directly modulated laser diodes are necessary for understanding and prediction of their performance in fiber-optical communication links. The alternatives based on a comprehensive experimental evaluation are normally costly and time consuming. This is particularly true for systems running at high bit-rate such as the 10Gb/s transmission systems that are used in tele and data communication applications. This thesis presents a modeling and simulation study for directly modulated laser diodes for high-speed fiber-optical communication systems. The work is based on the conventional rate equation model used as the governing equation for the simulation of the behavior of semiconductor lasers. In modeling of the system performance, each device is treated as a symbolic node that takes input signal and generates output signal all in time domain. For the semiconductor lasers, the original signals in electrical domain are taken as the input while the modulated lights in optical domain are as the output. The rate equations then link the output to the input. For any given time domain signal input, the modulated light (power and wavelength) as the output is calculated through the solutions of the rate equations. In seeking for the solution to the rate equations, we utilized a numerical approach to solve the rate equations which are a system of coupled nonlinear ordinary differential equations where analytical solution does not generally exist. In this work, a comprehensive study on the behavior of semiconductor lasers has been performed through static and dynamic analyses of the rate equations. The noise characteristic is also examined as it may become a major concern in some applications for the noise of the directly modulated laser transmitter may cause degradation to the signals and therefore lead to system penalty. Further, the numerical models and simulators developed for semiconductor lasers are incorporated into a general simulation platform on which similar models and simulators for other optoelectronic and optical components are connected to form a system-level simulator for point-to-point multiple channel fiber-optical communication links. This platform is capable of handling different system configurations with different component selection options. It simulates the time domain waveform in any point along the signal transmission path following a strict data-flow approach; i.e., the simulation is performed sample-by-sample on “real time” rather than frame-by-frame at “flush” mode. Finally, the simulation results, both on the device level and on the system level, have been compared with the experimental data and the results from other models in literature and found qualitative agreement.
Time-Domain Simulation of Semiconductor Laser
Keywords: time-domain simulation; semiconductor laser; laser; fiber-optic; communication systems; electrical and computer engineering; electrical engineering; computer engineering; fiber-optic communication systems